The key to my heart [large type] - Louis, Lia (Center Point Large Print, 2023)
"Sparkly and charming Natalie Fincher has it all - a handsome new husband, a fixer-upper cottage of her dreams, and the opportunity to tour with the musical she's spent years writing. But when her husband suddenly dies, all her hopes and dreams instantly disappear. Two and a half years later, Natalie is still lost. She works, sleeps (well, as much as the sexually frustrated village foxes will allow), and sees friends just often enough to allay their worries, but her life is empty. And she can only bring herself to play music at a London train station's public piano where she can be anonymous. She's lost motivation, faith in love, in happiness . . . in everything. But when someone begins to mysteriously leave the sheet music for her husband's favorite songs at the station's piano, Natalie begins to feel a sense of hope and excitement for the first time. As she investigates just who could be doing this, Natalie finds herself on an unexpected journey toward newfound love for herself, for life, and maybe, for a special someone."--